Extraction, Gene Regulation and Hypocholesterolemic Effects, and Antioxidative Activity of Thymoquinone Rich Fraction and Thymoquinone from Nigella Sativa (pdf incomplete) - Al-Naqeeb, Ghanya Naji (2009)
Nigella sativa and its active constituent thymoquinone (TQ) have been used for various health benefits such as antitumor, antidiabetic, antihypertensive, antioxidatative and antibacterial. The present study involves thymoquinone rich fraction (TQRF) prepared from Nigella sativa seeds using supercritical fluid extraction (SFE) and commercial available thymoquinone (TQ) to investigate their regulatory effects on genes involved in cholesterol metabolism in vitro using Human liver cancer cells (HepG2 cells) and in vivo using Sprague-Dawley rats. In the present study, SFE extraction procedures with different parameters of pressure at 400 and 600 bar and temperature at 40, 60 and 80°C were optimized to prepare TQRF. The yield of the oil content was highest (37%) at a high temperature of 80°C and a high pressure of 600 bars. The TQ content in different fractions of oil was the highest (2%) at a low temperature of 40°C and a high pressure of 600 bars compared to other used parameters. The major fatty acids in TQRF were oleic and linolenic which exist as unsaturated fatty acids. Palmitic, stearic and myristic acids were the main saturated fatty acids. TQRF was rich in α-tocopherol content (290 ± 1.5 mg/100g). HepG2 cells viability was determined using MTT assay and flow cytrometry. TQRF and TQ were shown to inhibit HepG2 cells growth with IC50 of 100 μg/ml for TQRF and 3.5 μg/ml for TQ after 72 h incubation. Flow cytometry analysis showed that the cells viability was more than 80% when HepG2 cells were treated with TQRF at 50 μg/ml and TQ at 2 μg/ml. The regulatory effects of TQRF at 50 and 80 μg/ml and TQ at 2 μg/ml on genes involved in cholesterol metabolism were studied in HepG2 cell using real time polymerase chain reaction. These genes included low density lipoprotein receptor (LDLR), 3-hydroxy-3-methylglutarylcoenzyme A reductase (HMG-COAR), apolipoproteins (Apo) including Apo A-1 and Apo B100. When cells were treated with TQRF at 50 and 80 μg/ml and TQ at 2 μg/ml mRNA level of LDLR gene was up-regulated by 3, 7 and 2 fold respectively, compared to untreated cells. On the other hand, mRNA level of HMG-COAR was down-regulated by 37, 71 and 12% respectively, compared to untreated cells. The mRNA level of Apo A-1 gene was up-regulated by 3, 4 and 2 fold and Apo B100 was suppressed by 60, 70 and 49% respectively, when cells were treated with TQRF at 50 and 80 μg/ml and TQ at 2 μg/ml compared to untreated cells. TQRF at dose of 0.5, 1 and 1.5 g/kg and TQ at 20, 50 and 100 mg/kg body weight in emulsion form were administrated orally to the rats fed diet supplemented with 1% cholesterol for 8 weeks. There was a significant reduction in plasma total cholesterol levels (TC) and low density lipoprotein cholesterol (LDLC) in both TQRF and TQ at different doses compared to cholesterol control rats (PC). The concentration of the alanine aminotransferase (ALT), gamma glutamyltranspeptidase (GGT), urea and creatinine of plasma collected from experimental rats were also measured in this experiment to test any toxic effect of TQRF and TQ on liver and kidney of rats. ALT, GGT and urea levels were significantly lower in TQRF and TQ treated groups compared to PC group. The antioxidant activity of TQRF and TQ treatment as hydroxyl radical (OH·) scavenging activity in plasma samples collected from experimental rats was also carried out using electron spin resonance (ESR). The findings showed significantly higher of OH· scavenging activity in TQRF and TQ treated rats at different doses compared to untreated rats. The regulatory effect of TQRF and TQ treatment on hepatic genes involved in cholesterol metabolism including LDLR, HMG-COAR, Apo A-1, Apo B100 and Apo E genes were also investigated in vivo. Treating rats with TQRF at dose of 0.5, 1 and 1.5 g/kg and TQ at 20, 50 and 100 mg/kg body weight showed up-regulation of LDLR and Apo E genes whereas both treatments in the same doses showed down-regulation of HMG-COAR and Apo B100 genes compared to untreated rats. In conclusion, the present study suggests that TQRF and TQ generated a hypocholesterolemic effect through regulation of key genes involved in cholesterol metabolism. Both in vitro and in vivo results demonstrate potential value of TQRF and TQ as a novel cholesterol lowering and antioxidant candidate.